Factors Affecting Uptake of COVID-19 Vaccines Among Adults: A Cross Sectional Survey - Sonia Pant; Susan Bergson; Smit Gade; Ella R. Gudwin (International Journal of Community Health Nursing And Practices, 2023)
The COVID-19 vaccination started in phased manner in India, and it was first time when a digital platform was developed for vaccine site registration. People had skepticism about newly developed vaccines and had poor understanding of using digital platform for vaccination registration. It was one of the reasons for poor vaccination coverage in marginalized section of the society. The pandemic has also affected other healthcare services as people were worried that they may get COVID-19 infection while visiting for healthcare services. Vision Spring conducts vision screening camps and provide affordable eyeglasses to marginalized section of the society, and referrals to the tertiary care hospitals. As COVID-19 vaccination campaigns began to roll out across India, VisionSpring proactively integrated COVID-19 vaccination counselling and awareness raising component into its vision outreach program. To understand the vaccination status and prevalence of vaccine hesitancy a cross sectional telephonic survey was conducted from October and November 2021 to understand the vaccination status and prevalence of COVID-19 vaccination hesitancy among the individuals screened through the vision screening program from the period October 2020 to March 2021. A total of 507 responses were randomly collected from Punjab, Rajasthan, and Uttar Pradesh outreach program locations and verbal consent was received from all individuals. Ninety one percent (n=459) were vaccinated with at least one dose, 33.3% (n=169) fully vaccinated with 2 doses, and 9.5%(n=48) were not vaccinated. Of those who were not vaccinated, of them 10.5% (n=26) female, and 8.5% (n=20) were male. Respondents who reported unvaccinated, of them 54% (n=26) do not want to take vaccine with the concerned about side effects.
Keywords: COVID-19; outreach program; vaccination; vaccine hesitancy; vision screening